Hepameta-- prevalence of hepatitis B/C and metabolic syndrome in population living in separated and segregated Roma settlements: a methodology for a cross-sectional population-based study using community-based approach - Gecková, Andrea Madarasová; Jarcuska, Peter; Mareková, Mária; Pella, Daniel; Siegfried, Leonard; Jarcuska, Pavol; Halánová, Monika; HepaMeta Team (Central European journal of public health, 2014)
BACKGROUND: Roma represent one of the largest and oldest minorities in Europe. Health of many of them, particularly those living in settlements, is heavily compromised by poor dwelling, low educational level, unemployment, and poverty rooted in generational poverty, segregation and discrimination. The cross-sectional population-based study using community based approach aimed to map the prevalence of viral hepatitis B/C and metabolic syndrome in the population living in separated and segregated Roma settlements and to compare it with the occurrence of the same health indicators in the majority population, considering selected risk and protective factors of these health indicators. METHODS: The sample consisted of 452 Roma (mean age = 34.7; 35.2% men) and 403 non-Roma (mean age = 33.5; 45.9% men) respondents. Data were collected in 2011 via questionnaire, anthropometric measures and analysed blood and urine samples. A methodology used in the study as well as in the following scientific papers is described in the Methods section (i.e. study design, procedures, samples, methods including questionnaire, anthropometric measurements, physical measurements, blood and urine measurements). CONCLUSIONS: There are regions of declining prosperity due to high unemployment, long-term problems with poverty and depleted resources. Populations living in these areas, i.e. in Central and Eastern Europe in Roma settlements, are at risk of poverty, social exclusion and other factors affecting health. Therefore, we should look for successful long-term strategies and tools (e.g. Roma mediators, terrain work) in order to improve the future prospects of these minorities.
Keywords: zdravotní stav; Metabolic Syndrome; mladý dospělý; Adult; Adolescent; hepatitida B; Prevalence; Young Adult; charakteristiky bydlení; Surveys and Questionnaires; lidé středního věku; mladiství; Romové; Cross-Sectional Studies; Socioeconomic Factors; Rural Population; Health Surveys; metabolický syndrom; průřezové studie; ženské pohlaví; prevalence; venkovské obyvatelstvo; Hepatitis C; lidé; socioekonomické faktory; hepatitida C; mužské pohlaví; Roma; Slovakia; chudoba; dospělí; Humans; Hepatitis B; Health Status; Poverty; Female; Middle Aged; zdravotnické přehledy; Male; Residence Characteristics; průzkumy a dotazníky; Slovenská republika